Improved Diabetes Control and Pancreatic Function in a Type 2 Diabetic after Omeprazole Administration - I. N. Mefford; J. T. Mefford; C. A. Burris (Case Reports in Endocrinology)
A 43-year-old man with type 2 diabetes, opposed to insulin use and poorly responsive to oral agents added sequentially over 6 years, was placed on 40 mg omeprazole twice daily. A linear decline in daily fasting blood glucose was observed over the first two-month treatment, and his hemoglobin A1c was reduced from 11.9% to 8.2%, then sustained at 8.1% after four months. Glucose, insulin, and C-peptide response to a 2-hour glucose tolerance test were consistently improved across this time period, and calculated beta-cell mass increased by 67%. We believe these responses are consistent with activation or neogenesis of pancreatic beta cells, possibly through a gastrin-mediated mechanism.